Effect of Ice Seeding on Slow Freezing of Ovarian Tissue - Ye Na; Xu Qiang; Liu Chenxi; Cao Yukun; Zhou Xinli (Zhileng xuebao)
Ovarian tissue cryopreservation is an important method for female fertility preservation. Slow freezing of ovarian tissue results in poor follicular survival and low retransplantation efficiency. This study optimized the ovarian tissue cooling procedure by ice seeding, and the effects of ice seeding temperature and cooling rate after seeding on ovarian tissue cryopreservation were analyzed. The programmed cooling apparatus was combined with an ultrasonic device to achieve the ultrasonic seeding of ice crystals, and the ultrasonic intensity was screened. The ovarian survival and histology were assessed after rewarming. The results revealed that the optimized cooling procedure with ice seeding reduced the damage to ovarian tissues. When ice seeding was triggered at -11 ℃ with a cooling rate of 1 ℃/min after nucleation, follicle survival was 88.02%. Ultrasonic nucleation equipment enabled contactless ice seeding of the samples, reducing the risk of contamination and improving the success rate of ice seeding. Furthermore, the follicle survival rate of frozen ovarian tissue increased to 88.38%. The optimization of the procedure and the improvement of the equipment improved the effect of ovarian tissue cryopreservation, reduced the risk of introducing contamination during the cryopreservation process, and provided a new method for the slow cryopreservation of ovarian tissues in clinics.